The Effect of Parents’ Income on Students’ English Achievement - Jannah, Miftakul; Yassin, Muhammad; Yolanda, Alvina (JURNAL JENDELA PENDIDIKAN, 2025)
This study aims to determine whether there is an effect of parents' income on student English achievement at Senior High School 1 Rasau Jaya. The research design used is Analysis Of Variance test, while the research method is quantitative. Discussion method as the independent variable (X) is parents’ income (low, Middle and High), while English learning achievement as the dependent variable (Y). The participants in this study were students selected using random sampling technique, namely students from Senior High School 1 Rasau Jaya totaling 100 people, namely 32 from the low income group, 36 students from the middle income group and 32 students from the high income group. Data in the study were collected using instruments (questionnaires), then assessed normality test, homogeneity test used to evaluate the requirements of data analysis. While analysis of variance analysis was used to test the hypothesis using computer software assistance through the SPSS (Statistcal Package for the Scial Sciens) version 24 for windows program. Based on the research findings and discussion, the following conclusions can be drawn: There is no effect of parents' Income on English Achievement. This is indicated by the result of the significance level of Analysis of variance 0.974 > 0.05. This shows that there is no influence between parents' income on student English achievement. This means Ho is accepted and Ha is rejected.